Polylactic acid/thermoplastic starch/montmorillonite nanocomposite : morphological, tensile properties, water absortion and degradation behavior - Jalalvandi, Esmat (2012)
Polylactic acid/ Tapioca starch/ Montmorillonite nanocomposites were prepared with different loadings of nanoclay (MMT) via twin screw extruder then compressed into plates for using in various tests. The effects of different loadings of MMT on mechanical, thermal, morphological properties, water absorption and biodegradation behavior of nancocomposites were investigated. Tensile properties were studied as some mechanical properties through this research. The thermal properties were characterized by using differential scanning calorimeter (DSC). Morphological properties of nanocomposites were studied through field emission scanning electron microscope (FESEM) and x-ray diffraction (XRD). Tensile strength increased by increasing the percentage of MMT in polymer matrix. Optimum amount for Young’s modulus and percentage of elongation at break were determined among the five samples and these results are in fine agreement with XRD results that prove the intercalated and exfoliated structure of nanocomposites. The results of DSC showed that MMT increased melting temperature and crystallization temperature of matrix but reduction in glass transition temperature was observed. During the water absorption test, amount of water intake decreased by increasing the content of MMT in nanocomposite structure. Biodegradation study exhibited that incorporation of this type of nanoclay has growing effect on degradation rate of nanocomposites.